2009
DOI: 10.1007/s10562-009-9979-x
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Stabilized by Task-Specific Oligomeric Ionic Liquid for Styrene Epoxidation Without Using VOCs as Solvent

Abstract: An oligomer of ionic liquid containing imidazolium and disulfide groups, which is miscible with the ionic liquid of [Bmim]PF 6 , was synthesized and used to stabilize gold nanoparticles. As such, epoxidation of styrene could be catalyzed by the oligomeric ionic liquidstabilized gold nanoparticles in the nonvolatile [Bmim]PF 6 without using any VOC as solvent. Under optimum reaction conditions, a styrene conversion of 100% with the selectivity to styrene oxide of 90% was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…They performed the nanoparticle synthesis by reducing HAuCl 4 with NaBH 4 in a mixture of butylmethylimidazolium hexafluorophosphate and the disulfide-imidazolium oligomer (Scheme 7). 118 Another example was provided by Mu et al, who developed a poly((N-vinyl-2-pyrrolidone)-co-(1-vinyl-3-alkylimidazolium halide)) copolymer (Scheme 8), to associate the imidazolium unit to the known noble metal surface stabilizer poly(N-vinyl-2-pyrrolidone).…”
Section: Functionalized Imidazolium Moieties For the Synthesis And St...mentioning
confidence: 99%
See 2 more Smart Citations
“…They performed the nanoparticle synthesis by reducing HAuCl 4 with NaBH 4 in a mixture of butylmethylimidazolium hexafluorophosphate and the disulfide-imidazolium oligomer (Scheme 7). 118 Another example was provided by Mu et al, who developed a poly((N-vinyl-2-pyrrolidone)-co-(1-vinyl-3-alkylimidazolium halide)) copolymer (Scheme 8), to associate the imidazolium unit to the known noble metal surface stabilizer poly(N-vinyl-2-pyrrolidone).…”
Section: Functionalized Imidazolium Moieties For the Synthesis And St...mentioning
confidence: 99%
“…Some of the preceding examples presented the development of hybrid systems associating imidazolium species with nanoparticles, whose distance from each other was rather well controlled by the structure of the surrounding organic part (Schemes 7, 14 and 15). 118,152,157 The control of the distances between nanoparticles is a key issue for many applications. 160,161 This distance between two nanoparticles has to be large enough for the nanoparticles not to agglomerate.…”
Section: Covalent Links Between Nanoparticles and Imidazoliummentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their well-established unique physicochemical properties, ILs are a subject of immense interest in the avenue of material, biological and chemical sciences [1][2][3][4][5][6][7]. ILs have been tested for their applicability in various fields such as in organic transformations [8], liquid-liquid extractions [9], gas adsorption and separation [10], as lubricant additives [11,12], as electrolyte in solar cells [13], and as solvent as well as template for dispersion and synthesis of nanoparticles, respectively [14] depending on the nature of constituent ions.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of selective oxidation of higher olefins catalyzed by supported gold catalysts, Choudhary et al [15][16][17][18][19] and subsequently Yin et al [20][21][22] have shown that gold nanoparticles supported on a range of carriers are active for the epoxidation of styrene using tert-butyl hydroperoxide (TBHP). About 50% selectivity to styrene oxide is achieved using this approach.…”
Section: Introductionmentioning
confidence: 99%